2016
DOI: 10.1039/c6gc01853j
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Catalysed conversion of carbohydrates to 5-hydroxymethyl furfural

Abstract: CO2 in water catalyzes the conversion of cellulose, starch, xylan, or glucose to HMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…On one hand, CO 2 is nontoxic; on the other hand, the use of an in situ‐generated carbonic acid catalyst avoids the typical drawbacks for both homogeneous and heterogeneous acid catalysts because it could be removed by simple depressurization and reused easily . For example, Lee et al . reported the use of a CO 2 ‐involved H 2 O‐CaCl 2 /1‐pentanol biphasic solvent for converting glucose (10 wt %) and a wide range of sugars into HMF, wherein CaCl 2 acts as a phase splitting agent whereas 1‐pentanol serves as an extractive phase for isolating HMF from the CO 2 ‐containg aqueous phase.…”
Section: Controlling the Reaction Network In Glucose Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, CO 2 is nontoxic; on the other hand, the use of an in situ‐generated carbonic acid catalyst avoids the typical drawbacks for both homogeneous and heterogeneous acid catalysts because it could be removed by simple depressurization and reused easily . For example, Lee et al . reported the use of a CO 2 ‐involved H 2 O‐CaCl 2 /1‐pentanol biphasic solvent for converting glucose (10 wt %) and a wide range of sugars into HMF, wherein CaCl 2 acts as a phase splitting agent whereas 1‐pentanol serves as an extractive phase for isolating HMF from the CO 2 ‐containg aqueous phase.…”
Section: Controlling the Reaction Network In Glucose Conversionmentioning
confidence: 99%
“…A highest HMF yield of 64.0 % with the carbon balance of 64.0 % has been achieved at 200 °C with an initial CO 2 pressure of 7.0 MPa. However, the imbalance of carbon demonstrated the formation of oligomers or insoluble humins . In addition, Fu et al .…”
Section: Controlling the Reaction Network In Glucose Conversionmentioning
confidence: 99%
“…6,15 However, CO 2 addition played an important role in the reaction as an acid catalyst, given that thermal conversion alone showed lower yields by comparison to CO 2 catalyzed aldol condensation. It has been shown previously by Lee et al 21 that CO 2 is an effective catalyst for the conversion of glucose to 5-HMF. Additionally, CO 2 catalysed conversion of polysaccharides of hexoses has been reported.…”
Section: -(5-hydroxymethyl-2-furyl)-3-butenone (Mono-aldolmentioning
confidence: 87%
“…It was previously found that an increase in aldol condensation product could be promoted by reducing the reaction pressure, as shown in Table 2. Additionally it was reported by Lee et al 21 that reducing the CO 2 pressure could also increases the 5-HMF yield from glucose. However, the effect of CO 2 pressure on the aldol reaction of glucose is unclear; at 1 wt% glucose, the yields are all very low and, within error, are the same for 2.5 and 15 MPa.…”
Section: -(5-hydroxymethyl-2-furyl)-3-butenone (Mono-aldolmentioning
confidence: 90%
See 1 more Smart Citation